2018
DOI: 10.1007/s11769-018-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation Ages Effect on Soil Physicochemical Properties and Heavy Metal Accumulation in Greenhouse Soils

Abstract: The intensive management practices in greenhouse production may alter the soil physicochemical properties and contribute to the accumulation of heavy metals (HMs). To determine the HM concentrations in vegetable soil in relation to soil physicochemical properties and cultivation age, we conducted a soil survey for typical greenhouse soils in Shouguang, China. The results indicated that Cd is a major HM pollutant in the tested soils, as the only HM element exceeding the allowed limit for vegetable soil. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Nonetheless, Cd exhibited a relatively higher environmental risk in the study area. As mentioned above, Cd had an over-standard rate of 16.1% and its maximum concentration was 43.7% higher than the limit (HJ333-2006), which is consistent with results from Zhang, et al [44] and Wang, et al [9] conducted in Baiyin (Gansu Province) and Shandong Province in China, respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, Cd exhibited a relatively higher environmental risk in the study area. As mentioned above, Cd had an over-standard rate of 16.1% and its maximum concentration was 43.7% higher than the limit (HJ333-2006), which is consistent with results from Zhang, et al [44] and Wang, et al [9] conducted in Baiyin (Gansu Province) and Shandong Province in China, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The Shouguang District is the largest base for greenhouse vegetable production in China, with an annual vegetable production of 4 × 10 6 tons [7]. Intensive management practices (e.g., more fertilizers and agrochemicals application, high multiple cropping index) in the greenhouse industry in this region have lasted for more than three decades, which has affected HM spatial distributions [8] and led to excessive accumulation of HMs [9] in greenhouse soils. Higher HM accumulations in greenhouse soils than in arable soils were also reported [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that an increasing PY of greenhouse cultivation increases the heavy metal concentrations in soil [ 40 ]. Chen et al (2016) also suggested that the heavy metal concentrations in soil increased over time as the years under cultivation increased [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has a higher output value and has been vigorously developed around the world, particularly in areas that are cold in the winter [1][2][3]. The higher rates of return have inspired farmers to apply large amounts of chemical fertilizers, organic fertilizers, and pesticides in facility agriculture production and adopt high-intensity planting methods, which result in a higher degree of intensive soil pollution than when the crops are cultivated in open fields [4][5][6][7][8][9][10][11]. Studies have shown that the content of elemental cadmium (Cd) in the soil of facility farmland in China currently exceeds the standard by much higher levels, and the degree of excess primarily exceeds the national standard in moderate and mild levels [9,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%